2020
DOI: 10.1029/2020ja028411
|View full text |Cite
|
Sign up to set email alerts
|

Global Propagation of Magnetospheric Pc5 ULF Waves Driven by Foreshock Transients

Abstract: Pc5 (2-7 mHz) ultralow frequency (ULF) waves play a significant role in resonating with particles and transferring energy in the coupled magnetospheric and ionospheric system. Recent studies found that Pc5 ULF waves can be triggered by foreshock transients which can perturb the magnetopause through dynamic pressure variation. However, whether foreshock transient-driven Pc5 ULF waves are geoeffective and can propagate globally is still poorly understood. In this study, we take advantage of the conjunction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 141 publications
(222 reference statements)
2
45
0
Order By: Relevance
“…Compared to the enhancements when the magnetopause is distorting outward around t ∼60 min, the perturbations generated by the inward magnetopause distortion around t 61.3 min are stronger and deeper into the magnetosphere. This shows that the magnetopause distortion driven by foreshock transients can launch compressional waves within the magnetosphere, which qualitatively explains the observed enhancements in magnetospheric ULF waves associated with foreshock transients (e.g., Hartinger et al, 2013;Wang et al, 2017;Wang et al, 2018b;Wang et al, 2019;Wang B. et al, 2020).…”
Section: Impact On the Magnetospherementioning
confidence: 62%
See 1 more Smart Citation
“…Compared to the enhancements when the magnetopause is distorting outward around t ∼60 min, the perturbations generated by the inward magnetopause distortion around t 61.3 min are stronger and deeper into the magnetosphere. This shows that the magnetopause distortion driven by foreshock transients can launch compressional waves within the magnetosphere, which qualitatively explains the observed enhancements in magnetospheric ULF waves associated with foreshock transients (e.g., Hartinger et al, 2013;Wang et al, 2017;Wang et al, 2018b;Wang et al, 2019;Wang B. et al, 2020).…”
Section: Impact On the Magnetospherementioning
confidence: 62%
“…The resulting magnetosheath perturbations and the impact on the dayside magnetopause have been simulated (e.g., Lin and Wang, 2005;Omidi et al, 2016;Sibeck et al, 2021)) and observed (e.g., Archer et al, 2014;Jacobsen et al, 2009;Kajdičet al, 2021;Sibeck et al, 1999;2000). Similar to the impact of the solar wind dynamic pressure perturbations, the magnetopause distortion driven by foreshock transients can subsequently generate ultralow frequency (ULF) waves inside the magnetosphere (e.g., Hartinger et al, 2013;Wang et al, 2017;Wang et al, 2018b;Wang et al, 2019;Wang B. et al, 2020;Shi et al, 2021;Wang B. et al, 2021), enhance particle precipitation and the resulting aurora brightness (e.g., Fillingim et al, 2011;Wang et al, 2018a;Wang et al, 2018b;Wang et al, 2019), and enhance field-aligned currents (FACs) and the associated perturbations in ionospheric currents and ground magnetic field (e.g., Kataoka et al, 2002;Murr and Hughes, 2003;Fillingim et al, 2011;Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Wang, Liu et al. (2020) has shown that there were significant oscillations started at ∼08:59:00 UT in the magnetic field (Figures 1a–1c and 1i–1k), electric field (Figures 1e, 1f, 1m, and 1n), and density (Figures 1g and 1o) observed by THEMIS A and D, respectively. During 09:03:45–09:04:35, both THEMIS A and D observed magnetosheath particles with density increasing to ∼9.5 cm −3 , which indicates a transient but significant compression with an inward motion of the magnetopause.…”
Section: Observations On October 30 2008mentioning
confidence: 91%
“…THEMIS A and D are close to the magnetopause in the magnetosphere, according to the strong magnetic field (∼55 nT; Figures 1a-1c and 1i-1k), low plasma density (∼0.6 cm −3 ; Figures 1g and 1o) and high energy ions (several tens keV; supporting information S1). Wang, Liu et al (2020) has shown that there were significant oscillations started at ∼08:59:00 UT in the magnetic field (Figures 1a-1c and 1i-1k), electric field (Figures 1e,1f,1m,and 1n), and density (Figures 1g and 1o) observed by THEMIS A and D, respectively. During 09:03:45-09:04:35, both THEMIS A and D observed magnetosheath particles (a-c) show the observation of (a) field-aligned, (b) azimuthal and (c) radial components of the magnetic field in field-aligned coordinate, respectively, observed by the time history of events and macroscale interactions during substorms (THEMIS) A.…”
Section: Observations On October 30 2008mentioning
confidence: 94%
“…As a result, when they encounter the bow shock, the local bow shock will move outward. Such perturbations can propagate into the magnetosheath and disturb the magnetopause and thus magnetosphere‐ionosphere system (e.g., Archer et al., 2014, 2015; Shen et al., 2018; Sibeck, Borodkova, et al., 1999; Turner, Eriksson, et al., 2011; B. Wang et al., 2018, 2020; Zhao et al., 2017a).…”
Section: Introductionmentioning
confidence: 99%